Black Immigrants in Portugal: LusoTropicalism and Prejudice - Vala, Jorge (2013)
This article analyzes the relationship between the luso–tropicalist representation of the history of Portuguese colonization and overt as well as covert expressions of anti-immigrant prejudice. The luso–tropicalist representation emphasizes the uniqueness of the Portuguese colonial relations based on Portuguese empathy and capacity to deal with people from different cultures. This representation was created during Salazar’s dictatorial regime and is still assumed to be a dimension of Portuguese national identity. The empirical findings presented in this article show that this luso–tropicalist representation may explain the salience of the norm against prejudice in Portugal and may contribute to weaken the traditional association between national identity and overt prejudice. A second dimension of the association between luso–tropicalism and integration of Black immigrants in Portuguese society was examined, that is, the impact of luso–tropicalism on the attribution and covert evaluation of cultural differences between White Portuguese and Black immigrants. Results show that despite the luso–tropicalist representation, White Portuguese individuals express a covert negative evaluation of cultural differences attributed to Black immigrants. This means that the luso–tropicalist representation can protect against the expression of overt prejudice but not against its covert dimensions.